(-2x+7)-(x+11)=

Simple and best practice solution for (-2x+7)-(x+11)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (-2x+7)-(x+11)= equation:


Simplifying
(-2x + 7) + -1(x + 11) = 0

Reorder the terms:
(7 + -2x) + -1(x + 11) = 0

Remove parenthesis around (7 + -2x)
7 + -2x + -1(x + 11) = 0

Reorder the terms:
7 + -2x + -1(11 + x) = 0
7 + -2x + (11 * -1 + x * -1) = 0
7 + -2x + (-11 + -1x) = 0

Reorder the terms:
7 + -11 + -2x + -1x = 0

Combine like terms: 7 + -11 = -4
-4 + -2x + -1x = 0

Combine like terms: -2x + -1x = -3x
-4 + -3x = 0

Solving
-4 + -3x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '4' to each side of the equation.
-4 + 4 + -3x = 0 + 4

Combine like terms: -4 + 4 = 0
0 + -3x = 0 + 4
-3x = 0 + 4

Combine like terms: 0 + 4 = 4
-3x = 4

Divide each side by '-3'.
x = -1.333333333

Simplifying
x = -1.333333333

See similar equations:

| 3x-7x+37=2x+31 | | 4x-5+2x+10+4x-5=180 | | (4+9)(-11)=121 | | -5=4k | | -3(c+2)+c=14 | | 1000=d-100 | | -5(1+7n)-n=-113 | | -8t+2t= | | 3/5*5/12= | | 9c+6=10c | | 2m+7-7=10+2m+18 | | -10=c-14 | | 11r-7s= | | 15(7c-5)=8c-3 | | 57=50x | | 38-3x=4x-18 | | Z-9=54.9 | | h=t^2+5t+6 | | 3x+8-12=2(2x-3)+x | | 1/2(3x2) | | 2/3x9/16 | | 7-5m=18+2m | | (5x-10)=37 | | 5(4+2x)+(-8x+-12)=68 | | (x+24)=(2x-1) | | 5x+24+9x-17=180 | | V+88=88 | | 2(3)+y=-3 | | 192x^2=108 | | 2(9-3z)-3(2z+9)=z-13 | | (5x-10)=360 | | 2(2)+y=-3 |

Equations solver categories